Indian adolescents’ perceptions of anaemia and its preventive measures: A qualitative study - Neha Rathi; Sangeeta Kansal; Aryan Raj; Nikitha Pedapanga; Immanuel Joshua; Anthony Worsley (Journal of Nutritional Science, 2024)
High prevalence of anaemia is a severe public health problem in several low- and middle-income countries like India. A qualitative inquiry was designed to understand the perceptions of adolescents regarding anaemia and anaemia prevention measures. Convenience sampling was employed to recruit 39 adolescents (19 girls; 20 boys) from Tikari, India. Interviews were carried out in the local language, audio-recorded and transcribed verbatim. Hemoglobin concentration was also assessed from a single drop of capillary blood using the HemoCue, and the participants were asked to share their Science/Biology and Home Science textbooks. Interview data was analysed thematically. Descriptive statistics were used to examine the distributions of the hemoglobin data while textbooks were analysed using content analysis to verify the coverage of anaemia and anaemia-related matter. Seven themes were identified: (i) Poor understanding of the term anaemia; (ii) Minimal discussion about anaemia in classroom; (iii) Limited knowledge about symptoms of anaemia; (iv) Limited awareness about prevention and cure of anaemia; (v) Perception of iron folic acid and deworming tablets among students; (vi) Lack of contribution of health workers in the prevention of anaemia; (vii) No knowledge of ‘Anemia free India’ programme. More than half of the sample had anaemia (16.7% mild anaemia, 33.3% moderate anaemia, 2.8% severe anaemia). Content analysis revealed that there was limited discussion about anaemia in both Home Science and Science textbooks. Behavioural interventions should focus on inculcating healthy culinary and dietary practices and addressing the gaps in knowledge and understanding of anaemia and its prevention among adolescents.